Women's Experience of Depressive Symptoms While Working From Home During the COVID-19 Pandemic: Evidence From an International Web Survey - Burn, Emily; Tattarini, Giulia; Williams, Iestyn; Lombi, Linda; Gale, Nicola Kay (Frontiers in Sociology, 2022)
The COVID-19 pandemic led to significant changes in workplace practices as social distancing requirements meant that people were asked to work from home where possible to avoid unnecessary contact. Concerns have been raised about the effects of the pandemic on mental health and, in particular, the effects of social distancing on employed women’s mental health. In this study, we explore the experiences of working women during the initial stages of the COVID-19 pandemic and explore the factors that may be associated with women experiencing the symptoms of depression. Findings from a cross-sectional survey of European working women (across five countries: France, Italy, Poland, Sweden and the UK) conducted between March and July 2020 are reported. The data are analysed using linear regression and mediation analysis. For women, working from home was associated with higher prevalence of the symptoms of depression compared to travelling to a workplace. The study also considers the mechanisms that may explain a relationship between working from home and depressive symptoms. Maintaining contact with people face-to-face and participating in exercise were both significant protective factors against experiencing symptoms of depression during a period of social distancing.